2005
DOI: 10.1111/j.1365-2842.2005.01451.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health‐related quality of life of stroke survivors on discharge from hospital after rehabilitation

Abstract: The study aimed to investigate oral health-related quality of life (OHR-QoL) of stroke survivors on hospital discharge after rehabilitation. It was a cross-sectional study involving 43 elderly survivors of mild to moderate stroke about to be discharged from hospital after rehabilitation and a comparison group of 43 community-dwelling elderly people. The Medical Outcomes Short Form 36 (SF-36) measure, the General Oral Health Assessment Index (GOHAI) and an oral health transition scale were administered prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 37 publications
(40 reference statements)
3
49
1
Order By: Relevance
“…25,27,34,37 A meta-analysis of pooled data, however, showed a significantly higher mean DMFT score among patients with stroke [standardized difference in means: 0.246, 95% CI (0.096-0.396), p = 0.001, both fixed and random effect, control group as reference] (Fig. 2b).…”
Section: Dental Caries Experience (Dmft)mentioning
confidence: 91%
“…25,27,34,37 A meta-analysis of pooled data, however, showed a significantly higher mean DMFT score among patients with stroke [standardized difference in means: 0.246, 95% CI (0.096-0.396), p = 0.001, both fixed and random effect, control group as reference] (Fig. 2b).…”
Section: Dental Caries Experience (Dmft)mentioning
confidence: 91%
“…2 McMillan et al 3 reported that upon hospital discharge following rehabilitation, approximately one-third of stroke survivors had diffi culty chewing hard food compared with before the stroke. In addition, according to Yoneyama et al, 4,5 oral care reduces pneumonia in older patients in nursing homes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the QOL scale has more often been used to study need assessments and plan oral health services (20)(21)(22)(23)(24). In this context, it is anticipated that increasing the available options for QOL scales will contribute to further development of QOL research in Japan.…”
Section: Introductionmentioning
confidence: 99%